A Randomized Trial of Progesterone in Women With Bleeding in Early Pregnancy. Issue 8 (August 2019) - Coomarasamy, Arri; Devall, Adam J.; Cheed, Versha; Harb, Hoda; Middleton, Lee J.; Gallos, Ioannis D.; Williams, Helen; Eapen, Abey K.; Roberts, Tracy; Ogwulu, Chriscasimir C.; Goranitis, Ilias; Daniels, Jane P.; et al.
Abstract : (Abstracted from N Engl J Med 2019;380:1815–1824) The hormone progesterone plays a critical role in preparing the endometrium for implantation of the embryo and continues to be produced throughout pregnancy. Historically, progesterone supplementation has been initiated during early pregnancies to prevent miscarriages in asymptomatic women who have a history of recurrent miscarriages or to rescue a pregnancy in women who have started to bleed during early pregnancy.